Maternal and neonatal outcomes following preterm birth: a retrospective cohort study - James Li; Matthew Davis; Kara M Rood; Vanessa Perez Patel; Eric Zuk; Damien Croft; Hyagriv N Simhan (Gynecology and Obstetrics Clinical Medicine)
Background Preterm births (PTBs) and associated costs in the USA are a public health concern. This study evaluated maternal and neonatal hospital-based outcomes, resource use and costs during delivery and up to 30 days postdischarge following PTB.Methods This study was conducted in the USA among individuals who delivered at ≥23 weeks gestation (1 January 2016–30 September 2021) captured in the Premier AI Healthcare Database. Linked neonatal data were used. Regression modelling and sensitivity analyses among spontaneous PTBs were performed. Costs were inflated to US$2022. In-hospital outcomes, resource use and costs were analysed.Results 4 303 772 deliveries were included; 14.8% were linked to neonatal records. Compared with term delivery, adjusted ORs for the <32 and 32 to <37 weeks gestation cohorts, respectively, were 1.33 (1.29–1.36) and 0.96 (0.95–0.98) for postpartum complications; 5.79 (5.58–6.01) and 2.73 (2.66–2.81) for maternal intensive care unit (ICU) admission; 4.20 (3.01–5.86) and 1.84 (1.38–2.46) for maternal death; 1.40 (1.37–1.43) and 1.01 (1.00–1.02) for maternal readmission; 76.92 (72.28–81.85) and 5.14 (5.03–5.25) for neonatal morbidity; 89.58 (84.59–94.87) and 10.07 (9.84–10.31) for neonatal ICU admission; 155.51 (130.98–184.63) and 8.81 (7.24–10.73) for neonatal death and 1.49 (1.41–1.58) and 1.16 (1.13–1.19) for neonatal readmission. Relative to term births, PTBs had significantly higher per-person maternal and neonatal resource use and costs. The results were robust to sensitivity analyses.Conclusions PTBs present a considerable maternal, neonatal and hospital burden compared with term birth.